2023
DOI: 10.3390/inorganics11010043
|View full text |Cite
|
Sign up to set email alerts
|

Heterogenous Preparations of Solution-Processable Cobalt Phthalocyanines for Carbon Dioxide Reduction Electrocatalysis

Abstract: The development and implementation of technology that can capture and transform carbon dioxide (CO2) is of ongoing interest. To that end, the integration of molecular electrocatalysts into devices is appealing because of the desirable features of molecules, such as the ability to modify active sites. Here, we explore how the identity of the aliphatic group in 1,4,8,11,15,18,22,25-octaalkoxyphthalocyanine cobalt(II) affects the catalytic behavior for heterogeneous CO2 reduction electrocatalysis. The alkyl R-gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…For dome-type distortions the average of the absolute values and average of the actual values should be approximately equal. Applying these structural metrics to the five-coordinate PcM (NHC) complexes herein, isoindole torsion angle ranges of −3.1(4) to 4.3(4), −6.3(4) to 7.2(4), and −4.5(3) to 3.0(3)°, N meso torsion angles of 6.55(6), 0.41 (7), and 3.74(5)°, average N-isoindole torsion angles of 0(5), 1(3), and 2(2)°, and averages of the absolute values of the N-isoindole torsion angles of 4(3), 2(2), and 2(1)°for PcCo II (DIP), PcZn II (DIP), and PcZn II (DMB), respectively (Fig. 4), were identified.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
See 1 more Smart Citation
“…For dome-type distortions the average of the absolute values and average of the actual values should be approximately equal. Applying these structural metrics to the five-coordinate PcM (NHC) complexes herein, isoindole torsion angle ranges of −3.1(4) to 4.3(4), −6.3(4) to 7.2(4), and −4.5(3) to 3.0(3)°, N meso torsion angles of 6.55(6), 0.41 (7), and 3.74(5)°, average N-isoindole torsion angles of 0(5), 1(3), and 2(2)°, and averages of the absolute values of the N-isoindole torsion angles of 4(3), 2(2), and 2(1)°for PcCo II (DIP), PcZn II (DIP), and PcZn II (DMB), respectively (Fig. 4), were identified.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…Phthalocyanines (PcH 2 ) have a diverse coordination chemistry and are used in applications ranging from colourants to electrocatalysts. [1][2][3][4][5][6][7][8] The simplest complexes are those of ringunsubstituted PcH 2 , for which many metal-substituted PcM congeners that span the periodic table are known. However, the extended π system, and the resultant rigid, planar structure of unsubstituted PcM complexes result in a strong tendency for them to aggregate.…”
Section: Introductionmentioning
confidence: 99%
“…To become a semiconductor, the two hydrogen atoms occupying the central ring can be replaced by a metal ion. The great stability in the redox processes of phthalocyanines attracts interest in using them in electrocatalysis processes [145][146][147][148][149][150][151]. Materials based on transition metal phthalocyanine have been extensively studied for the improvement of reactions involving oxygen (ORR and OER).…”
Section: Phthalocyaninesmentioning
confidence: 99%
“…Materials based on transition metal phthalocyanine have been extensively studied for the improvement of reactions involving oxygen (ORR and OER). Tajbakhsh, E., et al used cobalt phthalocyanines in reducing carbon dioxide [146]. Eyele-Mezui, S. et al used phthalocyanine tetrasulfonate intercalated in metal-layered simple hydroxides (metal: Co, Cu, and Zn) in the evaluation of the electrocatalytic activity, with a focus on fuel cells, where the materials showed potential [145].…”
Section: Phthalocyaninesmentioning
confidence: 99%
“…In work from our group, we explored the relationship between the degree of aggregation and the type of substitution at the α position [56]. In simple drop-cast preparations of 6-8 (Figure 5), we demonstrated that bulkier alkoxy-chains do not necessarily lead to better dispersion and, therefore, more facile access to active sites.…”
Section: Direct Electrode Adsorption/deposition and Catalyst Inksmentioning
confidence: 99%